86 National collaborative audit on excessive weight loss in the first three weeks of life – did the Covid-19 pandemic change outcomes?. (17th August 2022) - Clements, Rebecca; Levene, Ilana
Abstract : Aims: The average maximal early weight loss in exclusively breastfed babies is 5.5-8.6% 1 which is predominantly due to excretion of excess fluid as urine. Babies who experience difficulty establishing effective breastfeeding risk having higher levels of weight loss and hypernatraemic dehydration which can have significant morbidity and mortality. 2 Routine weighing is used to screen for babies at risk of dehydration at a premorbid stage and allow for enhanced support. Objectives: 1. To assess the impact of the Covid-19 Pandemic on rates of markers of significant dehydration in breastfed babies 2. To benchmark the rate of markers of significant dehydration in early life, to allow individual trusts to assess their own performance Methods: Audit criteria were developed by the Hospital Infant Feeding Network (www.hifn.org) and NHS Trusts across the UK were invited to participate. Each trust registered and performed the audit in line with local governance policies and reported aggregate anonymised outcomes. Inclusion criteria: Babies born ≥34 weeks' postmenstrual age who were assessed or treated in hospital with weight loss ≥12.5% and/or plasma sodium ≥155mmol/L in the first 21 days of life. Exclusion criteria: Exclusive formula feeding by day 3 of life and/or congenital abnormality affecting feeding, identified before day 3 of life. Data were collected for two six months epochs: 01/09/19-29/02/20 (pre-pandemic) and 01/04/20-30/09/20 (early pandemic). Analysis used Chi square test: Results: 13 NHS trusts from across the UK submitted data, representing approximately 29, 000 births in each epoch. All responding trusts were Unicef Baby Friendly Initiative accredited at Stage two or above. Routine weighing of babies varied between day 3-5, with the majority (73%) using ≥12.5% weight loss as the threshold for medical review. There was no statistically significant differences between rates of weight loss or serum sodium ≥155mmol/l between the two epochs. Data were therefore pooled for benchmarking: 0.8% of babies had ≥12.5% weight loss (approximating the 99th centile), 0.2% had ≥15% weight loss (approximating the 99.8th centile) and 0.1% had hypernatraemia ≥155mmol/l (approximating the 99.9th centile). Conclusion: This national collaborative audit is the first of its kind to provide benchmarking data for trusts to focus on their own service improvement. The rate of ≥12.5% weight loss found is consistent with that published by NICE, supporting the validity of the approach despite a skew towards Unicef accredited units in Southern England. There was no significant increase in excess weight loss or severe hypernatraemia during the early pandemic despite the disruption to breastfeeding support services - it is also known that national breastfeeding rates remained stable. 3 It is possible that an increase in dehydration in some babies due to poor breastfeeding support is masked by increased formula use in others, or by improved breastfeeding efficacy due to reduced competing demands. This is supported by other evidence showing a mixed picture of feeding outcomes for different families during the pandemic. 4 References: NICE Guideline 75. 2017. Laing IA. Archives F&N 2002;87:F158-F162. Harrison S. You and your baby: a national survey NPEU. 2021. Brown A. Mater Child Nutr . 2021;17 :e13088.